How Magnetic Composites are Effective Anticancer Therapeutics? A Comprehensive Review of the Literature - Yusefi, Mostafa; Shameli, Kamyar; Jahangirian, Hossein; Teow, Sin-Yeang; Afsah-Hejri, Leili; Mohamad Sukri, Siti Nur Amalina; Kuča, Kamil (International journal of nanomedicine, 2023)
Chemotherapy is the most prominent route in cancer therapy for prolonging the lifespan of cancer patients. However, its non-target specificity and the resulting off-target cytotoxicities have been reported. Recent in vitro and in vivo studies using magnetic nanocomposites (MNCs) for magnetothermal chemotherapy may potentially improve the therapeutic outcome by increasing the target selectivity. In this review, magnetic hyperthermia therapy and magnetic targeting using drug-loaded MNCs are revisited, focusing on magnetism, the fabrication and structures of magnetic nanoparticles, surface modifications, biocompatible coating, shape, size, and other important physicochemical properties of MNCs, along with the parameters of the hyperthermia therapy and external magnetic field. Due to the limited drug-loading capacity and low biocompatibility, the use of magnetic nanoparticles (MNPs) as drug delivery system has lost traction. In contrast, MNCs show higher biocompatibility, multifunctional physicochemical properties, high drug encapsulation, and multi-stages of controlled release for localized synergistic chemo-thermotherapy. Further, combining various forms of magnetic cores and pH-sensitive coating agents can generate a more robust pH, magneto, and thermo-responsive drug delivery system. Thus, MNCs are ideal candidate as smart and remotely guided drug delivery system due to a) their magneto effects and guide-ability by the external magnetic fields, b) on-demand drug release performance, and c) thermo-chemosensitization under an applied alternating magnetic field where the tumor is selectively incinerated without harming surrounding non-tumor tissues. Given the important effects of synthesis methods, surface modifications, and coating of MNCs on their anticancer properties, we reviewed the most recent studies on magnetic hyperthermia, targeted drug delivery systems in cancer therapy, and magnetothermal chemotherapy to provide insights on the current development of MNC-based anticancer nanocarrier.
Keywords: magnetické pole; Magnetic Fields; indukovaná hypertermie; Hyperthermia, Induced; hyperthermia; nádory; Drug Delivery Systems; targeted cancer treatments; external magnetic field; polymer-based magnetic nanocomposites; lidé; Neoplasms; magnetismus; Magnetics; magnetic nanoparticles; Humans; lékové transportní systémy